2019
DOI: 10.1016/j.corsci.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogen on the propagation of intergranular corrosion defects in 2024 aluminium alloy

Abstract: To study the influence of hydrogen on the intergranular corrosion mechanism of a 2024 aluminium alloy, samples were hydrogen precharged by cathodic polarisation and then exposed to a NaCl solution. EBSD analyses and SEM observations showed that hydrogen increased the number of corroded interfaces and led to the embrittlement of low-angle grain boundaries which were not susceptible to corrosion without hydrogen precharging. The increase of the reactivity of the 2024 aluminium alloy in the presence of hydrogen g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Regardless of the mechanism leading to local IM corrosion, the inevitable result is the formation of corrosion pits due to either dissolution of the particle (dealloying) or cathodic undermining (trenching) with consequent particle detachment (etch out) [23][24][25]. Further propagation of corrosion pits underneath the surface can in turn lead to intergranular attack of the grain boundaries and the nucleation of corrosion cracks [26][27][28][29][30][31][32]. Corrosion pits can therefore act as stress concentrators and reduce the load bearing capacity of the structure in question, eventually resulting in dramatic failures.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the mechanism leading to local IM corrosion, the inevitable result is the formation of corrosion pits due to either dissolution of the particle (dealloying) or cathodic undermining (trenching) with consequent particle detachment (etch out) [23][24][25]. Further propagation of corrosion pits underneath the surface can in turn lead to intergranular attack of the grain boundaries and the nucleation of corrosion cracks [26][27][28][29][30][31][32]. Corrosion pits can therefore act as stress concentrators and reduce the load bearing capacity of the structure in question, eventually resulting in dramatic failures.…”
Section: Introductionmentioning
confidence: 99%
“…For the as-received and deformed samples, the potential difference in GBPs was found to be higher than the matrix difference. GBPs form more galvanic microcells, leading to a higher amount of microgalvanic corrosion [53][54][55]. As can be seen in Figure 6, the initial microstructure showed fine precipitates homogeneously distributed in the sample.…”
Section: Correlation Between Scc Resistance and Gbpsmentioning
confidence: 94%
“…Liao et al [53] reported that the copper corrosion rate increases as the thin electrolyte layer (TEL) thickness decreases during the initial stages. Researchers studying the influence of hydrogen on the propagation of intergranular corrosion (IGC) defects of 2024 aluminum alloy concluded that H did not influence the elementary processes of IGC, although it had a significant impact on the local reactivity [54]. In addition to these factors, the evolved hydrogen seems to play a very important role in the degradation of the materials [34,35,55].…”
Section: Introductionmentioning
confidence: 99%
“…The preferential attack of these grain boundaries results in a specific corrosion mode named intergranular corrosion (IGC). Challenges relative to intergranular corrosion concern various materials such as nickel based alloys [1][2][3], aluminum based alloys [4][5][6] or steels [7][8][9]. One specific issue is about IGC of nonsensitized stainless steels (SSs) in nitric acid.…”
Section: Introductionmentioning
confidence: 99%